2021
DOI: 10.1021/acs.chemrestox.0c00452
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Cellular Zinc Status on PARP-1 Activity and Genomic Stability in HeLa S3 Cells

Abstract: Poly(ADP-ribose) polymerase 1 (PARP-1) is actively involved in several DNA repair pathways, especially in the detection of DNA lesions and DNA damage signaling. However, the mechanisms of PARP-1 activation are not fully understood. PARP-1 contains three zinc finger structures, among which the first zinc finger has a remarkably low affinity toward zinc ions. Within the present study, we investigated the impact of the cellular zinc status on PARP-1 activity and on genomic stability in HeLa S3 cells. Significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…These values are in agreement with the 0.5–1 nM free Zn 2+ that is typically observed for the concentration of free Zn 2+ in the cytosol of mammalian cells using fluorescence-based sensors and probes. 21 , 40 , 41 Note that the BLZinCh-Pro sensors are also expected to be attractive FRET sensors for live cell imaging using fluorescence microscopy. In comparison with the BLZinCh-1 and eZinCh-2 sensors, the BLZinCh-Pro sensors have an affinity that is better tuned to the concentration of free Zn 2+ in the cytosol, and they also display a larger change in the emission ratio between the Zn 2+ -free and Zn 2+ -bound states (700% change for BLZinCh-P40 compared to 400% for BLZinCh-1, Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…These values are in agreement with the 0.5–1 nM free Zn 2+ that is typically observed for the concentration of free Zn 2+ in the cytosol of mammalian cells using fluorescence-based sensors and probes. 21 , 40 , 41 Note that the BLZinCh-Pro sensors are also expected to be attractive FRET sensors for live cell imaging using fluorescence microscopy. In comparison with the BLZinCh-1 and eZinCh-2 sensors, the BLZinCh-Pro sensors have an affinity that is better tuned to the concentration of free Zn 2+ in the cytosol, and they also display a larger change in the emission ratio between the Zn 2+ -free and Zn 2+ -bound states (700% change for BLZinCh-P40 compared to 400% for BLZinCh-1, Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…As TPEN is a cell permeant, hydrophobic molecule it has the ability to produce harsh zinc depleted conditions. When used at concentrations higher than 2 μM, it causes cell apoptosis [20,37] . Using our NAN system to deliver TPEN has reduced its cytotoxic effect by delivering smaller amounts into the interior of the cell thereby avoiding the untargeted permeation of free TPEN.…”
Section: Resultsmentioning
confidence: 99%
“…However, as it is able to permeate through cell membranes, non‐targeted delivery of TPEN causes off‐target effects by interfering with the function of metalloproteins and produces a harsh metal depleted environment. Researchers have studied the pro‐apoptotic effect of TPEN in various cell lines and have reported that a low micromolar concentration of 3–5 μM of free TPEN is cytotoxic in nature [19,20,21] . Thus apart from the toxicity issues associated with TPEN, water‐insolubility and cell membrane permeability are some of the other many drawbacks that restricts researchers from exploring TPEN as a potential therapeutic agent [22,23] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, poly(ADP-ribose) polymerase 1 (PARP1) and p53 are well-known representatives of Zn-finger proteins, involved in safeguarding genome integrity [ [29] , [30] , [31] ]. Indeed, a recent study could determine the importance of Zn (signaling) in PARP1 activation finally resulting in genome stability maintenance [ 32 ].…”
Section: Introductionmentioning
confidence: 99%